Quantum-chemical simulation of low-temperature argon matrix with embedded water clusters - Vasylieva, A.O.; Doroshenko, I. Yu.; Bulavin, L.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
For the spectroscopic study of individual molecules or clusters, which do not interact with each other and with the environment, a method of matrix isolation in low-temperature matrices of inert gases is often used. However,numerous experimental investigations show that the positions of spectral bands in a matrix isolation can dif fer from the corresponding positions in the gas phase. This means that the structure of isolated molecules changes under a matrix influence. In order to determine the influence of an argon matrix on the positions of vibrational bands in the spectra of isolated water clusters, quantum-chemical calculations of the structure and infrared absorption spectra of solid argon matrix fragments with embedded water clusters of different sizes are carried out. Instead of considering the matrix environment as a continuous argon solution (as was done in our previous works), the following model is used: a fragment of the fcc argon crystal, several atoms of which are substituted by water molecules. For a monomer, one argon atom is substituted by one water molecule, for a dimer — two argon atoms are substituted by two water molecules, and so on. The geometry optimization of the obtained structures was made using the program set Gaussian 03 by M06-2X method with basis sets CRENBL ECP for argon and aug-cc-pVDZ for water molecules. Vibrational spectra of the corresponding structures are calculated at the same level of theory. By comparison of the obtained results with the calculated spectra of similar water clusters in vacuum, the influence of the argon environment on the vibrational spectra of water clusters in the matrix isolation is determined. It is shown that the presence of the matrix environment is manifested by shifting the spectral bands towards lower frequencies by several tens of wavenumbers relative to the corresponding vibrations in vacuum.